In Vitro Dissolution Interference Study in Presence of Paracetamol Tablets with Freshly Prepared Mango Juices on Simulated Gastrointestinal Digestion - Md. Didaruzzaman Sohel; Faisal Asif; Md. Helal Uddin Sumon; KanizFatema; Md. Hassan Kawsar (Journal of Pharmacy and Nutrition Sciences, 2020)
This study is performed beneath In Vitro dissolution applying various mathematical approaches to observe the dissolution interference on simulated gastrointestinal digestion. In total, eight medicine samples wereollected in Bangladeshi market and the conventional approaches were followed to measure the result in gastric medium (pH 1.2). Altogether, the brands showed sensibly upper dissolution discharge; primarily P01 (98.9%), P08 (98.97%), P03 (98.32%) and P06 (98.24%) were released relatively faster than the other sample in 15 to 60 minutes. Along with the mango juice in the simulated gastric medium, the brands showed sensibly upper dissolution discharge; primarily P01 (98.83%), P07 (98.98%), P06 (98.78%) and P03 (98.38%) were released relatively faster than the other sample in 15 to 60 minutes. This result depicts to understand the proper release of kinetics with the help of various mathematical model such as Zero order, First order, Higuchi and Hixson-Crowell model etc. although Paracetamol can interact with the fruit juices, which may alter the drug release, drug absorption in the body and may also lead to an unwanted reaction.